Development of Strategies to Support Parental Engagement In the Early Childhood Education Unit Partnership - Suardi, Suardi; Samad, Sulaiman (Universitas Negeri Makassar, 2021)
Providing education for early childhood is not enough only by maximizing the quality of activities in the classroom. Indeed, the parents' involvement should also be maximized. The study aimed to produce a valid and practical strategy prototype for the early childhood education unit to maximize the involvement of parents in a partnership program. This research and development using the Content Development Process-CDP model involved 202 subjects selected through purposive sampling technique. Research data were collected using a questionnaire, and the results were analyzed descriptively. Data analysis included calculating the percentage and average score and grouping data. The findings show that: (1) the development of the strategy to support the involvement of parents in early childhood education unit partnership is necessary because there is still a gap that needs to be solved in the partnership; (2) strategies to support the involvement of parents are divided into two clusters: the strategy to create family - friendly early childhood education; and preparing educators to work with families/parents. Each strategy cluster has core strategies with several action programs. The first strategy cluster consists of four core strategies with 13 action programs, while the second cluster strategy has two core strategies with seven action programs. Third, the results of the test performed by experts on the strategy prototype show that the product was in the valid / very feasible category. Also, the results of the test by target users show that the product was in the very practical category.